Inertial Sensor Self-Calibration Module for Autonomous Underwater Vehicle Navigation - Abd Kadir, Abdul Aziz; Abdul Kadir, Herdawatie; Isa, Khalid; Ambar, Radzi (Evolution in Electrical and Electronic Engineering, 2021)
The Autonomous Underwater Vehicles (AUV) industry is growing dramatically with the increase in the reliability and technical abilities of these vehicles. The vehicles require autonomous guidance and control system in order to perform underwater tasks. The Inertial Sensor Self-Calibration Navigation module is the important mission module that can be implemented into the navigation target, it permits the vehicle to follow preprogrammed trajectories wherever and whenever required. Without this module, the vehicle will not be able to achieve the desired mission. In this work, the Mission module need to be able to identify the task, detect the target, coordinate the state of AUV (attain desired height and yaw angle) and makes decision on path based on mission time elapsed. To navigate this Autonomous Underwater Vehicle (AUV), the navigation module selects Inertial Navigation System (INS). This navigation system used computers, accelerometers, gyroscopes, and sometimes magnetic sensors to calculate the dead reckoning, orientation and velocity (movement direction and speed) moving objects without external reference requirements. The AUV was able to navigate underwater and track underwater object without the need of operator assistance.